2018
DOI: 10.3390/su10082764
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial Vertebrate Biodiversity Loss under Future Global Land Use Change Scenarios

Abstract: Efficient forward-looking mitigation measures are needed to halt the global biodiversity decline. These require spatially explicit scenarios of expected changes in multiple indicators of biodiversity under future socio-economic and environmental conditions. Here, we link six future (2050 and 2100) global gridded maps (0.25 • × 0.25 • resolution) available from the land use harmonization (LUH) database, representing alternative concentration pathways (RCP) and shared socio-economic pathways (SSPs), with the cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 59 publications
(104 reference statements)
3
54
0
Order By: Relevance
“…Our estimates of the impact of land-use change on plant biodiversity are in broad agreement with those for vertebrate biodiversity based on a different SAR-based approach(Chaudhary & Mooers, 2018). Our estimates of the impact of land-use change on plant biodiversity are in broad agreement with those for vertebrate biodiversity based on a different SAR-based approach(Chaudhary & Mooers, 2018).…”
supporting
confidence: 72%
See 2 more Smart Citations
“…Our estimates of the impact of land-use change on plant biodiversity are in broad agreement with those for vertebrate biodiversity based on a different SAR-based approach(Chaudhary & Mooers, 2018). Our estimates of the impact of land-use change on plant biodiversity are in broad agreement with those for vertebrate biodiversity based on a different SAR-based approach(Chaudhary & Mooers, 2018).…”
supporting
confidence: 72%
“…It is important to clarify that this method, as for any other SARbased approach (Chaudhary & Mooers, 2018;Pereira & Daily, 2006), does not estimate the proportion of species that will go extinct within a specified time frame. Rather, the approach estimates the proportion of species which are expected to persist or become extinct over the long term, as a consequence of the climate and land-use conditions observed or predicted at a specified time point.…”
Section: Projecting Biodiversity Persistence Under Landuse and Climmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been found that agricultural exports from the Philippines to the United States rank eighth in terms of largest embodied biodiversity impacts globally (Chaudhary & Kastner, 2016). Bird extinction risks in the Philippines are also high due to tropical wood exports, and forests in Palawan island in particular are at high risk for biodiversity loss (Nishijima et al, 2016;Chaudhary & Mooers, 2018). These threats to biodiversity mean that the Philippines has significant challenges to meet increases in biomass demand without putting even higher strains on the ecosystems, particularly in light of population growth and dietary changes (Kastner & Nonhebel, 2010).…”
Section: Philippine Biodiversity Agriculture and Land-usementioning
confidence: 99%
“…In the future, the combined effects of both agricultural intensification and expansion will have serious consequences for biodiversity (e.g. Chaudhary & Mooers, 2018;Kehoe et al, 2017;Delzeit et al, 2017). One of the ways to mitigate habitat loss and its negative effects is forest conservation.…”
Section: Impacts Of Intensive Agriculture On the Environmentmentioning
confidence: 99%